2017
DOI: 10.1016/j.jvs.2016.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Volume of subclinical embolic infarct correlates to long-term cognitive changes after carotid revascularization

Abstract: OBJECTIVE Carotid intervention is safe and effective in stroke prevention in appropriately selected patients. Despite minimal neurologic complications, procedure-related subclinical microemboli are common and their cognitive effects are largely unknown. In this prospective longitudinal study, we sought to determine long-term cognitive effects of embolic infarcts. METHODS 119 patients including 46% symptomatic patients who underwent carotid revascularization were recruited. Neuropsychological testing was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 35 publications
2
36
0
1
Order By: Relevance
“…Selection bias-free randomisation could be considered either unethical (in the case of high-risk lesion randomisation in a study employing prior generation single-layer stent(s) now DW-MRI evidenced to be associated with cerebral embolisation significantly exceeding, in both incidence and volume, that of a mesh-covered stent system [ 5 , 60 ]), or the study would be a priori likely to be inconclusive (in case of low-risk patient lesion randomisation). Cerebral DW-MRI imaging is going to continue [ 35 , 38 , 40 , 43 , 55 , 60 , 67 ] to provide a sensitive and clinically-relevant [ 76 , 79 , 80 , 83 ] surrogate in the evaluation of novel carotid revascularisation technologies and treatment strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection bias-free randomisation could be considered either unethical (in the case of high-risk lesion randomisation in a study employing prior generation single-layer stent(s) now DW-MRI evidenced to be associated with cerebral embolisation significantly exceeding, in both incidence and volume, that of a mesh-covered stent system [ 5 , 60 ]), or the study would be a priori likely to be inconclusive (in case of low-risk patient lesion randomisation). Cerebral DW-MRI imaging is going to continue [ 35 , 38 , 40 , 43 , 55 , 60 , 67 ] to provide a sensitive and clinically-relevant [ 76 , 79 , 80 , 83 ] surrogate in the evaluation of novel carotid revascularisation technologies and treatment strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding is thus increasing today that the total burden of DW-MRI-depicted microembolisation in patients undergoing carotid revascularisation by CEA or CAS may be associated with transient cognitive decline [ 82 ]. In a proportion of patients, part of the deficit may persist months after the intervention [ 82 , 83 ]. Thus, any carotid intervention, to have a positive impact on brain function, needs to be associated with minimised cerebral embolism.…”
Section: Diffusion-weighted Magnetic Resonance Imaging and Mesh-covermentioning
confidence: 99%
“…5 These "silent lesions" are relevant for their association with cognitive decline. 6 These two limitations indicate that the frequency of new cerebral events after CEA, symptomatic or not, was probably underestimated in the current study.…”
mentioning
confidence: 70%
“…These lesions are clearly identifiable as procedure-related because they appear immediately after the procedure, are typically visible for only a few days, and have been related to particles flowing to the brain and detected on carotid ultrasound ( Bonati et al, 2010 ; Ederle et al, 2010 ; Poppert et al, 2006 ; Rapp et al, 2007 ; Skjelland et al, 2009 ; Tedesco et al, 2009 ). Clinically, endovascular procedures are effective means of preventing stroke, and whereas serious associated complications are rare ( Brott, 2010 ), there have been inconsistent studies suggesting these lesions may be linked to subtle post-procedural cognitive decline and increased vulnerability to future cognitive declines ( Aharon-Peretz et al, 2003 ; Fink et al, 2015 ; Ghogawala et al, 2008 ; Heyer et al, 1998 ; Tiemann et al, 2009 ; van Dijk and Kalkman, 2009 ; Wasser et al, 2011 ; Zhou et al, 2017 ; Zhou et al, 2012 ). For example, one large study showed changes in hand dexterity related to side of intervention ( Heyer et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%